The Profile Of Vital Lung Capacity On Ujung Kulon National Park Professional Divers - Arief Nuryadin; Ayu Rahayu; Qory Jumratul 'Aqobah (Universitas Bengkulu, 2021)
This research aims to describe the profile of vital lung capacity of professional divers in Ujung Kulon National Park. This type of research is descriptive with a cross sectional approach. The research subjects in this study is all population of professional divers in Ujung Kulon National Park, totaling 24 people with varying age categories, ranging from 20-29 years, 30-39 years, 40-49 years, to 50-59 years. The data collection techniques in this research were carried out by interviewing, questionnaire, and lung vital capacity tests using spirometer. The data were analyzed by means of descriptive analytic. Based on the results of the spirometry test, it is known that only 12.5% of professional divers have FVC %pred, FEV1%pred and the FEV1 / FVC ratio are in the normal category, two people in the 30-39 year age range, and one person in the age range. 50-59 years. Another 87.5% experienced have restriction and obstruction symptoms. The degree of restriction and obstruction disturbance experienced by divers also varies according to age range category.